Corrosion behaviour of point‐by‐point wire and arc additively manufactured steel bars. Issue 7 (10th February 2022) - Michel, Lucas; Sanchez, Asel M. A.; Silvestru, Vlad‐Alexandru; Ariza, Inés; Taras, Andreas; Angst, Ueli
Abstract: Robot‐assisted point‐by‐point wire and arc additive manufacturing is considered a promising technology for optimising the production of metallic connections used in complex nodes, space trusses or grid shells. While mechanical properties of such elements were proved suitable for structural applications, a lack of knowledge exists concerning their durability. We investigate the corrosion performance of low carbon steel bars produced by point‐by‐point wire and arc additive manufacturing. Metallurgical analyses show uniform microstructure along the length of the steel bars. Corrosion initiation tests in simulated atmospheric exposure reveal the influence of geometry on corrosion, in particular, the presence of concave areas. The surface state and postprinting cleaning processes were investigated with microscopy and electrochemical techniques. These experiments indicate a detrimental effect of oxide scales due to the wire and arc additive manufacturing process on the corrosion behaviour of the steel. The results of the study show that special care must be given to the geometry and surface state of wire and arc additively produced low carbon steel components in case of long‐term use. Abstract : This study is focused on the durability performances of low carbon steel bars produced with point‐by‐point wire and arc additively manufacturing technology. In particular, the corrosion behaviour is investigated. The influence of the geometry and postprinting cleaning process are identified as key parameters in the case of long‐term use of wire and arc additively manufactured low carbon steel components.